A Literature Review of Relieves from Yoga Regarding Irregular Menstruations and Complications of Menarche - Niroshanee, S.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
Yoga is beneficial to both men and women. The current problem prevailing in the society is as infertility following irregular menstruation. Hence the study was made to overcome the problem by yoga to avoid miserable circumstances faced while menstruations. Before or during the menstruation they have some sign and symptoms. Some yoga helps to prevent from the complications. Irregular menstruation also a very big problem in nowadays. Some yoga helps to relief from the problems. They are Salapasanam, Thanurasanam, Passhimoththasanam, Khalasanam, Sarvangasanam, Mathsyasanam, Savasanam and Nadi sutty. They gave relief from feeling tried, sleeping disturbance, abnormalities of stomach (constripation, diarrhea and bloating), headache, backache, poor appitite, joints and muscles pain, fatigue and stomach pain. The asanas not only relief from the complications but also prevent from the infertility. So according to the study the above yoga will give good relieves to women during the menstruations times and helps to prevent from infertility.
Keywords: Yoga; Irregular menstruation; Infertility